2013
DOI: 10.1002/jgrc.20172
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal distribution, along‐channel transport, and post‐riverflood recovery of salinity in the Guadalquivir estuary (SW Spain)

Abstract: [1] This paper presents an experimental analysis of the salinity distribution, the salt balance, and the variation of the saline intrusion in comparison to the freshwater discharge in the Guadalquivir estuary, which is a mesotidal system regulated and normally subjected to extremely low river flows. In such low-flow conditions, it is positive, well-mixed, and tidally dominated. The estuary is also characterized by a nonstationary, effective longitudinal dispersion coefficient, whose probability density becomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 49 publications
2
40
1
Order By: Relevance
“…The values Kh,i employed are Kh,i=1754 normalm2/s for i=5,6 and Kh,i=963 normalm2/s for the rest of the boxes, similarly to those obtained for salinity in Díez‐Minguito et al . []. A sensitivity analysis is performed on these parameters.…”
Section: Formulation and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The values Kh,i employed are Kh,i=1754 normalm2/s for i=5,6 and Kh,i=963 normalm2/s for the rest of the boxes, similarly to those obtained for salinity in Díez‐Minguito et al . []. A sensitivity analysis is performed on these parameters.…”
Section: Formulation and Methodologymentioning
confidence: 99%
“…Under normal or low river flow conditions, i.e., with freshwater flows below 40normalm3/s, this is a tidally energetic estuary, which results in well‐mixed conditions, except for a partial stratification in the mouth area. A vertically sheared circulation is observed, but its effects on the salt transport are clearly lesser than the tidal effects [ Díez‐Minguito et al ., ]. The analysis of the stratification‐circulation parameters under normal conditions establishes a Type‐2a estuary according to the scheme of Hansen and Rattray [].…”
Section: Introductionmentioning
confidence: 99%
“…Taylor (1954) showed that the interaction between the vertical gradient of velocity and vertical mixing could lead to the horizontal dispersion of salt or other contaminants. This shear dispersion theory was applied in many estuarine studies to explain the mechanism of tidal oscillatory salt transport (Bowden 1965;Fischer 1976;Uncles et al 1985;McCarthy 1993;Díez-Minguito et al 2013). Tidal shear dispersion is important when the time scale of vertical or transverse mixing is comparable to the tidal time scale (Fischer et al 1979;Geyer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most field studies have measured the response of only a limited number of biological, chemical, hydrodynamic or geomorphic parameters. The pioneering study of Nichols (1977) and the later studies of Eyre (Eyre & Twigg 1997;Hossain et al 2001) and Diez-Minguito et al (2013) are notable for their scope and careful treatment of the data. Such detailed case studies can provide a basis for management and, more generally, guidance on the processes that must be retained in a model and those of lesser importance that may be approximated or omitted.…”
mentioning
confidence: 99%